Meningkatkan Pengetahuan Dengan Ilmu dan Teknologi Yang Berkualitas - Nurdin, Almiansyah; Nugraha, Heru Arif; Muharam, Ijhmal Patwa; Mulyana, Irfan Anwar; Nugraha, Moch Rifaldi Hakiki; Pratama, Rama; Exiana, Rega Muhammad; Erlangga, Ridwan Juansyah; Ahmadi, Salman Fariz; Cikal, Septian Reinaldo; Lukmana, Tedi; Fadli, Dicky Muhamad (Institut Teknologi Garut, 2022)
COVID-19 is still very rampant in human life right now, it's been almost 2 years that the world has been haunted by a pandemic that still doesn't know when it will end. This pandemic greatly affects and limits every community activity, various sectors are hampered due to the restrictions that the Government has imposed. The education sector is no exception, due to the pandemic, teaching and learning activities have become difficult to carry out because face-to-face meetings are not permitted. Anxiety about the spread of the virus due to crowds of people is the reason all activities involving large numbers of people are stopped. Because studying at school will gather many people, online learning is enforced in all regions in Indonesia. With this policy, the knowledge of the community, especially workers and students, is reduced. Therefore, online activities were also made, namely through webinar activities with the aim and hope of helping increase public knowledge. In this case, the topic raised originates from problems in the community environment related to the field of study of interest, namely civil engineering. The method as an indicator to determine the level of public knowledge is through the pretest and posttest forms. In this form several questionnaires are given regarding the material that will be discussed in the webinar activity, so that data and graphs of the level of public knowledge are obtained.